Effects of different pre-treatments on the extraction of pectin from pomelo (Citrus maxima) peels and rinds. - Descalsota, Jr. Alex Oñates (2014.)
The study seeks to assess the effects of pre-treatments on the efficiency of extraction of pectin from pomelo (Citrus maxima) peels and rinds in terms of percent yield. There were five pre-treatments applied which include freezing, drying, soaking, steaming and fresh (control) was established. The pectin produced was characterized in terms of setting time determination, spreadability of jelly, color of the extracted pectin and FT-IR spectrum analysis. Drying as a pre-treatment was found to be the most efficient pre-treatment on extraction of pectin of percent yield (2.61%), which was higher than the percent yields of other four pre-treatments. Setting time and spreadability were significantly different between the five pre-treatment techniques at 5% level of significance. Further comparison using post hoc analysis revealed that the untreated sample was the sole pre-treatment being significantly different from the other pre-treatment (less than p = 0.05) Direct relation was observed between the setting time of the gel pectin and the spreadability of the jelly i.e., the longer the setting time of the gel pectin, the higher the spreadability of the jelly and vice versa. The color of the extracted pectin was affected by the pre-treatments, as the pre-treatments eliminates or reduces impurities which cause darkening in the pectin in both undried and dried pectin. The FT-IR (AVATAR 330 Fourier Transform Infrared Spectrometer Thermo Nicolet) spectrum analysis revealed that the experimental samples were pectin. In the spectrum analysis for the pre-treated pectin from pomelo peels and rinds, a weak intensity of Aromatic rings was perceived while a strong and a broad in O-H as well in C=O and medium intensity of Alkane (C-H). The five pre-treatments exhibits same pattern of the spectra but varies in wavenumbers. This submits that pre-treatments did not have a significant effect on the spectra of polysaccharides from pomelo peels and rinds.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Pectin; Pomelo; Citrus maxima